The Role of Sharia Capital Markets in Driving National Economic Growth - Ahmad Dani Husni (STAI AN-NAJAH INDONESIA MANDIRI, 2024)
The capital market is a market for various long-term financial instruments that can be traded, either in the form of debt or equity. The financial instruments traded in the capital market include stocks, bonds, warrants, rights, convertible bonds and various derivative products such as options (put or call). The existence of the capital market is a reality and a current phenomenon in the midst of the lives of Muslims in this modern century. Viewed from the sharia side, the capital market is one of the means or products of muamalah. Transactions in the capital market, according to sharia law principles, are not prohibited, as long as there are no transactions that conflict with the provisions outlined by sharia. Among them are transactions that contain interest and usury. Sharia also prohibits transactions that contain speculation and contain garar or ambiguity, namely transactions in which fraud is possible. The sharia capital market has emerged as an investment alternative that is not only in accordance with Islamic principles, but also contributes significantly to national economic growth. This article discusses the role of the sharia capital market in driving economic growth with a qualitative approach through literature studies. It was found that Islamic capital markets can increase liquidity, attract investors, and support financing of sustainable projects. Keywords: sharia principles, investment ethics, economic stability